Role of landslides on the volume balance of the Nepal 2015 earthquake sequence - A. Valagussa (Nature Portfolio, 2021)
Abstract The 7.8 Mw earthquake that struck Nepal on April 25th, 2015 triggered over 21,000 landslides over an area of more than 25,000 km2. These landslides contributed to mass wasting, partially compensating the tectonic uplift by the earthquake. In this paper we quantify the volume balance resulting from the 2015 earthquake uplift (or subsidence) and landslide erosion. Starting from a new complete earthquake-induced landslide inventory, we calculated landslide volume by adopting different strategies for low-mobility and high-mobility landslides, considering also the potential supply of sediments to the drainage network. The results show that the contribution of earthquake-induced landslides to erosion is about one order of magnitude smaller than the vertical coseismic displacement. We found landslide volume values, due to the 2015 Nepal earthquake, ranging between 251 (− 15/ + 16) Mm3 up to 1503 (− 183/ + 210) Mm3 based on the adopted method, and a volume due to coseismic vertical displacement of 2134 (± 1269) Mm3 for the whole area. The volume balance of the 2015 Nepal earthquake is strongly dominated by tectonic displacement. We show that these estimates depend on several uncertainties. We identified and quantified uncertainties related to: (1) the choice of empirical volume-area scaling relationships and their parameters; (2) the completeness and quality of landslide inventory through comparison with available inventories; (3) the approach adopted for the assessment of elongated landslide volume; (4) the InSAR displacement data.